Representações do sujeito feminino em presença de Thalia, de Ruth Laus : regionalidade, cultura e subjetividade - Rocha, Karen Gomes da (My University, 2015)
This dissertation focuses on the representations of the female figure in Presença de Thalia (1989), by Ruth Laus, a writer from Santa Catarina, dialoguing and relating to issues inherent to the identity and the space of fictional representations of gender, the female subject as a producer of texts and fictional character, as well as evaluates the interference of patriarchal ideology present in the novel. To seek answers to the question of what is the feminine, the analysis of masculine and feminine, among other combinatorial possibilities, enables a critical view through research and analysis, on breaking, or not, the mythical model of patriarchy. Therefore, it is analyzed the regional setting and its cultural interrelations in the novel, first, from theoretical assumptions regarding the region and regionality; then, combined with the perspective of feminist criticism, are used as subsidies the studies of Showalter (1994) and the anthropologists Bruner (1986) and Geertz (1989), in order to, by focusing on the female authorship text, that is, her expression, regarding the evaluation of family court and social power structures established fictionally, to unveil the conceptual structures and interpret the culture's fictional web of symbols; and, finally, basing the discussions on representation, identity and subjectivity with the assumptions of Chartier (2002) and Weedon (2003), reveal how female subjects are conceived.
A presente dissertação focaliza as representações da figura feminina em Presença de Thalia (1989), da escritora catarinense Ruth Laus, dialogando e relacionando com questões inerentes à identidade e ao espaço das representações ficcionais entre gênero, o sujeito feminino enquanto produtora de textos e personagem ficcional, assim como avalia a interferência da ideologia patriarcal presente na obra. Para buscar resposta ao questionamento do que é o feminino, pela análise do mascullino e do feminino, entre outras possibilidades combinatórias, viabiliza-se uma visão crítica por meio de pesquisa e análise, acerca da ruptura, ou não, do modelo mítico do patriarcado. Para tanto, analisa-se a configuração regional e as suas interrelações culturais na obra, primeiramente, a partir de pressupostos teóricos sobre região e regionalidade; depois, aliados à perspectiva da crítica feminista, utilizam-se como subsídios os estudos de Showalter (1994) e dos antropólogos Bruner (1986) e Geertz (1989), com o intuito de, ao evidenciar o texto de autoria feminina, isto é, sua expressão, no que concerne à avaliação do campo social familiar e as estruturas de poder estabelecidas ficcionalmente, desvelar as estruturas conceptuais e interpretar as “teias de relações” ficcionais; e, finalmente, embasando as reflexões sobre representação, identidade e subjetividade, os pressupostos de Chartier (2002) e Weedon (2003), revelar como são concebidos os sujeitos femininos.
Keywords: Análise do discurso; Regionalismo na literatura; Literatura brasileira - Ficção; Feminismo; Discourse analysis; Regionalism in literature; Brazilian literature - Fiction; Feminism